Service Industry Databook Understanding and Analyzing Sector Specific Data Across 15 Nations - Elango, B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Locating empirical information on specific service industry characteristics is not an easy task, even for an individual familiar with various sources of data. This book is a quick source of information on service industry statistics across many nations of the world. The reader is introduced to finding key sources of data, building analytical ratios from diverse sources, and understanding the advantages and disadvantages of data selection methods in the service sector. The global nature of the data compiled in this book, especially an extensive coverage of the United States, makes it an invaluable resource to active researchers and stakeholders in the service industry as well as those who seek to enter it.
Introduction -- Potential Sources of Data on the Service Sector -- United States Service Sector Data -- Service Sector Data on 14 OECD Nations -- Global Service Sector Data -- Drivers of Profitability in Service Sector.
Keywords: Business; Service industries; Data mining; Statistics; Business and Management; Services; Statistics for Business/Economics/Mathematical Finance/Insurance.; Data Mining and Knowledge Discovery; Electronic books